Metabolomic and Lipidomic Profiling of Preoperative CSF in Elderly Hip Fracture Patients With Postoperative Delirium - Han, Yongzheng; Zhang, Wenchao; Liu, Jiao; Song, Yanan; Liu, Taotao; Li, Zhengqian; Wang, Xiaoxiao; Yang, Ning; Li, Yue; Han, Dengyang; Mi, Xinning; Zhou, Yang; et al. (Frontiers in Aging Neuroscience, 2020)
Objective To investigate dysregulated molecules in preoperative cerebrospinal fluid (CSF) of elderly hip fracture patients with postoperative delirium (POD), in order to identify potential pathological mechanisms and biomarkers for pre-stage POD. Methods This nested case control study used untargeted metabolomic and lipidomic analysis to profile the preoperative CSF of patients (n = 40) who developed POD undergone hip fracture surgery (n = 10) and those who did not (n = 30). Thirty Non-POD patients were matched to ten POD patients by age (± 2 years) and Mini Mental State Examination score (± 2 points). CSF was collected after successful spinal anesthesia and banked for subsequent analysis. On the first two postoperative days, patients were assessed twice daily using the Confusion Assessment Method-Chinese Revision. CSF samples from the two groups were analyzed to investigate possible relevant pathological mechanisms and identify candidate biomarkers. Results Demographic characteristics of the groups were matched. Eighteen metabolites and thirty-three lipids were dysregulated in the preoperative CSF of POD patients. Pathway enrichment analysis revealed perturbations in D-glutamine and D-glutamate metabolism; glycerophospholipid metabolism; alanine, aspartate and glutamate metabolism; sphingolipid metabolism; histidine metabolism; and arginine biosynthesis at the pre-delirium stage. Receiver operating characteristic curve analysis indicated that phosphatidylethanolamine (PE, 40:7e), with an area under the curve value of 0.92, is a potential biomarker for POD. Conclusion Multiple pathological mechanisms in the POD group were involved before surgery, including neuroinflammation, oxidative stress, and energy metabolism disorders induced by hypoxia, as well as neurotransmitter imbalances such as increased dopamine and glutamate, and decreased glutamine. These metabolic abnormalities potentially increase the fragility of the brain, thus contributing to POD. PE (40:7e) might be a potential biomarker for POD. Not only do our results provide potential biomarkers for POD, but also provide information for deep pathological research. Clinical trial registration: This study was registered in the Chinese Clinical Trial Registry (ChiCTR1900021533).